Kampanye Diversitas perempuan "Undefineable" Victoria Secret - Ezarine Vani Indira Pawestry (Jurnal Ilmu Komunikasi, 2022)
The presence of women in the Victoria's Secret lingerie industry for decades has been met with controversy and scandal. Starting from sexual harassment, bullying, misogyny and treatment of women. Especially how they refused to add an element of diversity to their runway models presented by the direct head of Victoria's Secret. But after the executives responsible for the scandal steps down. Victoria's Secret launching The VS Collection, the company learned to add an element of diversity to its models by creating campaign called undefinable by proclaiming “Nothing can define us. Not your standards. Not your stereotype. Not your fantasy. Not anymore." This research uses a qualitative descriptive type approach with the Thwaites textual analysis method, which interprets a visual communication in terms of denotation, connotation and myth. Through this method the researcher tries to analyze post-rebranding visual marketing texts with the marketing strategy carried out by Victoria's Secret. This research will refer to how the politics of women's bodies, women in the media, and the value of diversity itself. The diversity context that will be discussed contains elements of body positivity, body acceptance, aging, disabled bodies and masculine women. This research was conducted to find out whether this company movement is true -really implement the values of diversity or just covering it up only for the benefit of capitalists from the company's side. Every company will definitely target sales, but not necessarily the campaign that is carried out is truly in accordance with its objectives.